The facticity of the for-other from the perspective of gaze and shame - Silva, Carlos Henrique Carvalho (Argumentos - Revista de Filosofia, 2025)
This article aims to understand the primordial experience of the existence of the Other, presented by Jean-Paul Sartre in the third part of Being and Nothingness. In order for our intention to be effectively understood, we have organized this reading into three duly articulated moments. In the first moment, it is essential to clarify how the French philosopher delimited the problem of solipsism as an obstacle constituted by realist and idealist philosophies that generally deny the conditions of possibility for the existence of the other, as well as the critical description that questions the permanence of solipsistic theories in contemporary times, bequeathed by Husserl, Hegel and Heidegger. From this critique, we will lead our reading to the second moment, which consists of establishing an understanding of the existence of the Other, showing how it appears and affects the subject’s daily life, above all because the Other requires the presence of a body and a consciousness that is distinct from the subject’s. In the last moment, we will emphasize the interesting approach to the gaze and shame, this original feeling that strips the consciousness of any certainty that it is isolated in the world. Thus, the experience of shame comes to be understood as the unveiling of the subject’s consciousness, which perceives itself as “invaded” by the gaze of the Other, thus making the Other’s existence in the concrete relationship effective.